Effects of α-amylase supplementation on production performance, blood metabolites, nutrient digestibility, and rumen fermentation parameters of Holstein dairy cows in late lactation - Zhang, Mengen; Li, Guodong; Wang, Dian; Wang, Shiqin; Du, Hongsheng; Lan, Rubing; Xu, Yiming; Liu, Hongkai; Li, Yingli (Frontiers in Veterinary Science, 2025)
Current research on dairy cows primarily focuses on peak lactation, with limited exploration of late lactation. This study investigated the effects of α-amylase supplementation on production performance, blood metabolites, nutrient digestibility, and rumen fermentation in late-lactation Holstein cows. Thirty cows (average milk yield: 37.48 ± 1.63 kg; parity: 2.44 ± 0.70; lactation days: 210.17 ± 2.20) were randomly divided into two groups: the control group (CON) received a basal diet, while the experimental group (AM) was supplemented with 15 g/day α-amylase for 7 weeks (1-week adaptation + 6-week trial). Results showed that α-amylase significantly increased milk yield, energy-corrected milk (ECM), and milk protein yield (p < 0.01) and improved fat-corrected milk (p < 0.05). Milk protein content, total solids, and milk fat yield also tended to rise (p = 0.061, p = 0.067, p = 0.091, respectively). No significant differences were observed in dry matter intake (DMI), feed efficiency, or somatic cell count. Serum amylase concentration increased markedly in the AM group (p < 0.01), while other blood parameters remained unchanged. Starch digestibility improved significantly (p < 0.05), and neutral detergent fiber (NDF) digestibility showed a positive trend (p = 0.063). Rumen propionate concentration rose significantly (p < 0.05), with no major changes in pH, ammonia nitrogen, or acetate-to-propionate ratio. In conclusion, α-amylase supplementation in late lactation enhances nutrient digestibility, modulates rumen fermentation, and improves production performance, offering metabolic regulation potential for extending high productivity in late-stage lactation.